Pengaruh Likuiditas, Agency Cost Dan Kebijakan Dividen Terhadap Nilai Perusahaan - Syaharany, Nabila; Maulana, Agus (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2024)
This research is quantitative research which aims to determine the effect of liquidity, agency costs and dividend policy on company value with profitability as a control variable. The population of this research is property and real estate sector companies listed on the Indonesia Stock Exchange for the 2019-2021 period. This research uses 159 samples were obtained using the purposive sampling method. Random Effect Model (REM) with multiple linear regression is used in this research using STATA 13. The results of this research are that liquidity does not have a significant effect on company value, agency costs do not have a significant effect on company value, dividend policy does not have a significant effect on company value, and profitability does not have a significant effect on company value.